Women's participation and representation in Nigeria's politics in the last decade (1999-2009) - Olatunde, Diane (My University, 2010)
ABSTRACT The world of politics has for a long time been regarded as a place reserved for men. However today, there is a growing agitation for doors to open for women in politics. And as can be expected various countries are working towards women participation and representation in politics, even their inclusion in areas of decision making in governance. This study examines one aspect of the state of gender equality in the Nigerian political setting namely the level of female participation and representation in the country’s politics from 1999-2009. This work is inspired by the changes in Nigerian politics within the stated time frame, with the return of uninterrupted civil rule after many years of military interventions. This achievement has brought with hope for an inclusive government, a government that recognizes all irrespective of gender, class or tribe. Today democracy is the order of the day, and this research reveals how women have fared so far, it reveals the extent to which democratic values have been applied as regards women and politics or gender equality in the area of Nigerian politics. In other to establish this, this study amongst other things focuses on the hypothesis that political parties contribute a lot to the low level of participation and representation of women in a representative democracy. It looks closely at the role of political parties in determining women’s level of access, presence and influence in the Nigerian political arena, by using the three major political parties in Nigeria as case studies. Furthermore, the study reveals how various measures aimed at enhances women’s participation and representation in politics established in the last decade have been implemented especially within the parties and the influence they have had.